Distribution of duchene muscular dystrophy in India - Dantuluri, S.; Дантулурі, Срініваса Раджу (Запорізький державний медичний університет, 2016)
Introduction: Duchene Muscular Dystrophy is a hereditary muscular disorder, characterised by the gradual weakening and loss of muscle cells. In boys it results in a risk of various life threatening complications. Goal: To create more awareness on Duchene Muscular Dystrophy and its distribution in India. Method – literature: Having done numerous researches using Wikipedia and many other sources.